2002
DOI: 10.1152/jn.00770.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regional Analysis of Whole Cell Currents From Hair Cells of the Turtle Posterior Crista

Abstract: Regional analysis of whole cell currents from hair cells of the turtle posterior crista. J Neurophysiol 88: 3259 -3278, 2002; 10.1152/jn.00770.2001. The turtle posterior crista is made up of two hemicristae, each consisting of a central zone containing type I and type II hair cells and a surrounding peripheral zone containing only type II hair cells and extending from the planum semilunatum to the nonsensory torus. Afferents from various regions of a hemicrista differ in their discharge properties. To see if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
46
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 69 publications
13
46
1
Order By: Relevance
“…Estimates of reversal potential confirmed that the currents were carried primarily by potassium. In terms of kinetics, activation range, and potassium selectivity, these currents were similar to those carried by the fast inward rectifier G K1 found in postnatal mouse vestibular hair cells (Rüsch et al, 1998) and hair cells of other organs and species (Ohmori, 1984;Fuchs and Evans, 1990;Masetto et al, 1994;Holt and Eatock, 1995;Sugihara and Furukawa, 1996;Marcotti et al, 1999;Brichta et al, 2002). To estimate the inward rectifier conductance, we used the peak current at Ϫ124 mV divided by driving force (V M Ϫ E 1 ϭ 42 mV).…”
Section: Inward Rectifier Conductancementioning
confidence: 71%
See 1 more Smart Citation
“…Estimates of reversal potential confirmed that the currents were carried primarily by potassium. In terms of kinetics, activation range, and potassium selectivity, these currents were similar to those carried by the fast inward rectifier G K1 found in postnatal mouse vestibular hair cells (Rüsch et al, 1998) and hair cells of other organs and species (Ohmori, 1984;Fuchs and Evans, 1990;Masetto et al, 1994;Holt and Eatock, 1995;Sugihara and Furukawa, 1996;Marcotti et al, 1999;Brichta et al, 2002). To estimate the inward rectifier conductance, we used the peak current at Ϫ124 mV divided by driving force (V M Ϫ E 1 ϭ 42 mV).…”
Section: Inward Rectifier Conductancementioning
confidence: 71%
“…Because a systematic variation in single-channel conductance as a function of age is unlikely, the parsimonious interpretation suggests that the increased density results from an increase in the number of functional potassium channels. Therefore, we suggest that the data can be best explained by the developmental acquisition of a homogeneous variety of voltage-dependent potassium channels with properties similar to the delayed rectifier seen in mature postnatal type II hair cells (Lang and Correia, 1989;Rennie and Ashmore, 1991;Masetto and Correia, 1997;Rüsch et al, 1998;Masetto et al, 2000;Brichta et al, 2002). However, we cannot exclude the possibility that the channels consist of a consistent ratio of heterogeneous channel subunits whose stoichiometry is tightly regulated.…”
Section: Delayed Rectifier Conductancementioning
confidence: 88%
“…Regardless of the explanation for the asymmetry, it seems reasonable to suppose that the relative sizes of the preblock inhibition and the postblock excitation reflect a balance between the density of nicotinic and SK channels. Other potential contributory factors include calcium buffering (Allbritton et al, 1992;Wu et al, 1996), the role of the cisterns and other internal stores in calcium regulation Lioudyno et al, 2004), and the presence of inward rectifiers (Brichta et al, 2002) that can limit hyperpolarizing responses (Robinson and Siegelbaum, 2003).…”
Section: Hair-cell Inhibition Is Similar In Vestibular and Nonvestibumentioning
confidence: 99%
“…A T-type channel has not been seen in hair cells (Ló pez et al, 1999;Martini et al, 2000;Bao et al, 2003) (but see Nie et al, 2005). IRK channels are seen in both the turtle crista (Brichta et al, 2002) and frog vestibular organs (Holt and Eatock, 1995;Marcotti et al, 1999), but IRK currents do not show a depolarizing overshoot after a hyperpolarization (Marcotti et al, 1999). I H is a candidate in the turtle posterior crista because it is only present in type II hair cells that would synapse on BM units (Brichta et al, 2002) and can give rise to both a hyperpolarization sag and a posthyperpolarizing depolarization (Robinson and Siegelbaum, 2003).…”
Section: Postinhibitory Excitation May Involve a Hyperpolarization-acmentioning
confidence: 99%
See 1 more Smart Citation